Architecting high performing, scalable and available enterprise web applications - Shivakumar, Shailesh Kumar (Morgan Kaufmann, an imprint of Elsevier, 2015)
This book provides in-depth insights into techniques for achieving desired scalability, availability and performance quality goals for enterprise web applications. It gives an integrated 360-degree view of achieving and maintaining these attributes through practical, proven patterns, novel models, best practices, performance strategies, and continuous improvement methodologies and case studies. --